Auditoría de gestión al área de comercialización de banano y su incidencia en la rentabilidad de la compañía Delindecsa S.A. Cantón Guayaquil, año 2012 - Soria Brito, Jimena Betsabeth (2015)
The purpose of the research was performed to evaluate the area Delindecsa Marketing Company SA of Guayaquil through a Management Audit to determine the shortcomings affecting the efficiency and effectiveness of activities and hence profitability, this will allow corrective action to help improve business performance. For this development research applied methods systematic, inductive, deductive, and analytical building on bibliographic field research, with the instruments used observing the process of commercialization, as well as the collection of data was applied by interviewing managers and surveys of officials of the study area. The results found in the study showed that there are weaknesses in the area of Marketing of bananas; thereof which are: poor internal control as revealed by the evaluation based on the COSO I model, giving a high risk level of 56.80%, which limits the efficient accomplishment of goals. The level of efficiency and optimization of resources through management indicators. It is not being constantly monitors. Therefore when applied in the implementation of the audit showed a low level of compliance of 17.23% and in relation to profitability in the year 2012. Managers were intended to reach 30%, but only 17.85% was obtained, reflecting a moderate level of compliance of 59.50% due to counter these factors the entity has failed to establish the ranking of the best banana exporting country. Therefore it is suggested to analyze the diagnosis presented and implement the recommendations set out in this research work.